Adoção e uso do governo eletrônico: o papel da confiança e confiabilidade - Barbosa, Johny Davyd Soares (2020)
The present study has as main objective to analyze the impact of trust and trustworthiness in the intention of adopting and using electronic government services. To meet this objective, it is proposed to answer the following question: what is the influence of trust and trustworthiness in the intention to adopt and use electronic government services? For this, a distinction was made between the concepts of trust and trustworthiness in the electronic government literature, in addition was made a review of the models of adoption and use of services in general and of electronic government in particular. The study proposed an e-government adoption model applied to the Brazilian context and which considered the concepts of trust and trustworthiness. The equation modeling technique was used and applied through partial least square with the application of a questionnaire composed of 36 items with 11-point Likert scales that were arranged in 10 constructs adapted from the specialized literature on the topic. The questionnaire was applied entirely online. The study confirmed 9 of the 12 hypotheses that were suggested. Among the hypotheses that have been confirmed are 2 hypotheses that address that trust in government and trust in the internet are necessary factors for the creation of trust in electronic government. Hypotheses that stated that ability, integrity and experience are important factors in building trust in government were confirmed by the study, while hypotheses that addressed benevolence and disposition to trust as important factors for trust in government have not been confirmed. This result demonstrates the importance of addressing trust in the process of formulating and implementing public policies. In addition, the study also confirmed the hypothesis that states that trust in e-government mitigates the risk perceived by citizens in relation to e-government services. In addition, the hypotheses also confirmed that e-government and the perceived risk are important for citizens' intention to use in relation to e-government services. Finally, these results demonstrate the necessary factors for the creation of trust and that it, according to the literature consulted at study, is essential for citizens to choose to use these types of government services.